III. Surface Condition of the Ice Sheet in the Mizuho Plateau-West Enderby Land Area, East Antarctica, 1969-1971 - ワタナベ, オキツグ; アゲタ, ユタカ; WATANABE, Okitsugu; AGETA, Yutaka (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper